2022
DOI: 10.21608/ejdr.2023.172741.1118
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hyssop (Hyssopus Officinalis L.) Plant Under Mariout Conditions - Egypt

Abstract: ield research was conducted on Hyssop (Hyssopus officinalis L.) plants in the Mariout region, North of Egypt during the two successive seasons of 2020 and 2021. The purpose of the study is to determine the optimum space, chemical fertilization, and their interactions on the biomass yield. The research was set compatible to a split-plot design technique. The inter spacing was 30 and 50 cm, while the subplots had chemical fertilization at three levels: full dose NPK, 2/3 NPK, and 1/3 NPK. The used chemical ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…However, wider spacing promotes the growth of more woody stems than leaves, resulting in a lower essential oil percentage than closer spacing. Conversely, the maximum yield of fresh and dry herb and essential oil per hectare resulted from planting in the narrow space of 30 cm due to an increased number of plants per unit area and oil percent, positively affecting production (Toaima, 2022). These findings were consistent with the research on rosemary that Mishra et al (2009), Zigene et al (2012), and Tadesse (2019) concluded through dense cultivation of plants.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, wider spacing promotes the growth of more woody stems than leaves, resulting in a lower essential oil percentage than closer spacing. Conversely, the maximum yield of fresh and dry herb and essential oil per hectare resulted from planting in the narrow space of 30 cm due to an increased number of plants per unit area and oil percent, positively affecting production (Toaima, 2022). These findings were consistent with the research on rosemary that Mishra et al (2009), Zigene et al (2012), and Tadesse (2019) concluded through dense cultivation of plants.…”
Section: Discussionsupporting
confidence: 81%
“…The research on rosemary and other medicinal herbs belonging to the Lamiaceae family revealed that the agricultural practices used to grow these plants significantly influence the plant's overall productivity and active components. According to Peter (2012) and Toaima (2022Toaima ( , 2023, agronomic methodologies are the primary factor determining the amount and quality of crude herbal products. This is due to the influence of agricultural treatments on photosynthetic efficiency and metabolic byproducts.…”
Section: Introductionmentioning
confidence: 99%